Identification and characterization of a potyvirus isolated from siratro plants - Regatier, L. J. [UNESP]; Gaspar, J. O. [UNESP]; Belintani, P. [UNESP]; Yuki, V. A. (Blackwell Publishing, 2008)
The present work describes the identification and characterization of a potyvirus isolated from siratro (Macroptilium atropurpureum Urb.) in the north-west region of the State of Sdo Paulo, Brazil. The virus was transmitted by mechanical inoculation. Its host range was restricted mainly to members of the Fabaceae. A cDNA fragment of about 930 bp was amplified by RT/PCR, cloned and sequenced. The fragment, which included the coat protein gene, had amino acid identity percentages between 88 and 98% with isolates of Bean common mosaic virus (BCMV). Phylogenetic analysis grouped the. siratro potyvirus and BCMV isolates in 99% of the replicates, including Azuki mosaic virus, Dendrobium mosaic virus, Blackeye cowpea mosaic virus and Peanut stripe virus, which have been classified as BCMV strains. This is the first citation on the presence of BCMV in siratro plants in Brazil.
Keywords: macroptilium atropurpureum; Plant virus; RT-PCR; sequencing; Brazil